Improved ChIP Sequencing for H3K27ac Profiling and Super-Enhancer Analysis Assisted by Fluorescence-Activated Sorting of Formalin-Fixed Paraffin-Embedded Tissues - Nenggang Jiang; Zhihao Wen; Huan Tao; Hongyan Liao (Biological Procedures Online)
Abstract Archived clinical formalin-fixed paraffin-embedded tissue (FFPE) is valuable for the study of tumor epigenetics. Although protocol of chromatin immunoprecipitation coupled with next generation sequencing (NGS) (ChIP-seq) using FFPE samples has been established, removal of interference signals from non-target cell components in the samples is still needed. In this study, the protocol of ChIP-seq with purified cells from FFPE lymphoid tissue of nodal T follicular helper cell lymphoma, angioimmunoblastic type (nTFHL-AI) after fluorescence-activated cell sorting (FACS) was established and optimized. Essential steps included single cell preparation, heat treatment enhancing antigen retrieval and labeling, cell sorting, chromatin shearing, ChIP and NGS. Through assistance of FACS, we successfully isolated tumor cells from FFPE lymph node samples of nTFHL-AI and profiled super-enhancers (SEs) mapping by enrichment of H3K27ac signals. The data indicated that the SEs mapping of the sorted cells was different from that of the entire unsorted tissue sample. The H3K27ac signals with cell lineage specificity from background cell components were successfully removed, and the remaining SEs mapping was more similar to T follicular helper cell in an unsupervised clustering analysis, rather than the primary tissue. In addition, we also evaluated the protocol using cultured pure cell lines, and the results indicated that the sequencing data obtained through this protocol had high fidelity and reproducibility. These results show that ChIP-seq for H3K27ac profiling and SEs mapping assisted by FACS with pathological FFPE tissue is available for research of histone modification. Precise epigenetic characteristics of the tumor cell can be described with this protocol.